Penerapan Strategi Pembelajaran Aktif Index Card Match (ICM) untuk Meningkatkan Hasil Belajar IPA di Kelas IX-5 MTs Negeri 2 Makassar - Supiana, Supiana (Universitas Negeri Makassar, 2017)
The objective of this research are: 1) To increase students' activity during the implementation of learning science through the application of active learning strategies index card match 2) To improve science learning outcomes of students after the application of active learning strategies index card match. This research is a classroom action research. Data were analyzed using descriptive analysis. From the results of the study showed that the students' learning activities during the application of active learning strategies index card match in the first cycle only reached an average percentage of 52.99% (20 active students from 37 number of students overall). While student learning outcomes after application of active learning strategies match the index cards learning science subject matter Reproductive System In Humans in cycle 1 only reached 13 students who completed (35.13%) and 24 students who did not complete (64.87%) with the overall average value 59.72. In the second cycle, namely increased activity of students with average percentage has reached 90.52% (34 active students from 37 number of students overall) while the learning outcomes of students increased by 29 students who completed (78.37%) and 8 students not completed (21.63%) with an overall average of 70.77. Thus concluded that by applying active learning strategies index card match increased studentÂ Learning outcomes.